On some generalizations of Baer’s theorem - Kurdachenko, L.A.; Pypka, A.A. (Carpathian Mathematical Publications, 2014)
In this paper, we obtained new automorphic analogue of Baer's theorem for the case when an arbitrary subgroup A≤ Aut(G) includes a group of inner automorphisms Inn(G) of agroup G and the factor-group A/Inn(G) is co-layer-finite.